THE ROLE OF GEOGRAPHICAL MAPS IN TERRITORIAL DISPUTES BETWEEN JAPAN AND KOREA - Arnon Medzini (European Journal of Geography)
Geographic maps and cartographic representations have become the new battle arenas where countries contest claims regarding territorial ownership, the exact location of borders and the names of disputed places. This paper analyzes the role of traditional and digital maps in asserting national identity and reinforcing claims of ownership by examining the case of Dokdo Island (South Korean name) or Takeshima Islands (Japanese name). According to the research findings, both countries understand that maps from earlier imperialistic periods have no legal value in proving their claims of sovereignty. Nevertheless, both make extensive use of historical maps as perceptual and propaganda weapons in order to gain a moral advantage in presenting their territorial claims as well as to shape the collective national consciousness.